Effectiveness of Acceptance and Commitment Therapy on Marital Boredom and Self-Compassion in Emotionally Divorced Women: A Quasi-Experimental Study - Khosravi Saleh Baberi , Fatemeh; Pasha , Reza; Heidari , Alireza; Bavi , Sasan (Advances in Nursing & Midwifery, 2021)
Abstract Introduction: Marital boredom and emotional divorce cause a gradual reduction in the emotional attachment of couples which is associated with feelings of alienation, apathy, and indifference between couples and replacement of positive emotions with negative ones. The present study aimed to investigate the effectiveness of acceptance and commitment therapy (ACT) on marital boredom and self-compassion in emotionally divorced women. Methods: This quasi-experimental study was conducted using a pretest-posttest control group design. Forty women were selected using convenience sampling and were randomly divided into intervention (n=20) and control (n=20) groups. The participants filled the Emotional Divorce Questionnaire, the Marital Boredom Scale, and the Self-Compassion Scale in the pre-test and post-test. The intervention group received eight 90-minute sessions of ACT. Data were analyzed using a one-way analysis of covariance. Results: Results suggested that ACT improved marital boredom (F=372.714 and P<0.001) and self-compassion (F=353.178 and P<0.001) in the post-test. The mean ±SD post-test scores of marital boredom and self-compassion in the experimental group were 43.30±4.45 and 42.95±4.75, respectively, which improved compared to the post-test of the control group. Conclusions: Based on the results, holding ACT workshops may exert beneficial effects on reducing marital conflicts.